Analisis Parameter Sandblasting terhadap Kekasaran Permukaan pada Material Baja A36 Menggunakan Metode Taguchi - Isna Aulia Kharisma; Farizi Rachman; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Sandblasting is a surface cleaning process by shooting particles in the form of sand on the surface of the material, causing the material to become clean and rough. In industrial manufacturing companies where there is a structural fabrication process, of course, it will go through a sandblasting process to determine whether or not the quality of the products produced is feasible. Where to produce products with good quality, the resulting surface roughness value must be high. The sandblasting parameters used are spraying pressure, spraying time, and abrasive material size in working with A36 steel material which is one of the materials for making structural fabrication. This research uses the Taguchi method, which is one of the experimental design methods that can be used in controlling the quality of a product. With this method, the optimum parameters will be sought with the larger is better criterion. From the experimental results, it was found that the parameters that affect surface roughness are spraying pressure and abrasive material size with a percentage contribution of 66.81% and 27.60%, respectively, while the spraying time parameter did not affect surface roughness but contributed 3.30%.